Characterization of structure and thermophysical properties of three ESR slags. (July 2016) - Plotkowski, A.; deBarbadillo, J.; Krane, Matthew J. M.
Abstract: The structure and properties of electroslag remelting (ESR) slags were characterized. Slags samples of three compositions were obtained from industrial remelting processes at Special Metals Corporation and from casting in a laboratory vacuum induction melter. The structure of the slag samples was observed using optical and electron microscopy, and phases were identified and their relative amounts quantified using X-ray diffraction. Laser flash thermal diffusivity, density, and differential scanning calorimetry measurements for specific heat were performed to determine the bulk thermal conductivity of the samples. Sample porosity was measured as a function of depth using a serial sectioning technique, and a onedimensional computational model was developed to estimate the thermal conductivity of the fully dense slags. These results are discussed in context with previous studies, and opportunities for future research are identified. AFRL Case Number: 88ABW-2015-1871.